MO074: SGLT2 Inhibition Promotes Intrinsic Kidney Regeneration by Cells of the Renin Lineage. (3rd May 2022) - van der Pluijm, Loïs; Koudijs, Angela; Stam, Wendy; Rotmans, Joris; Gross, Kenneth W; Paul Pieper, Michael; Jan van Zonneveld, Anton; Bijkerk, Roel
Abstract: BACKGROUND AND AIMS: With chronic kidney disease (CKD) prevalence rapidly increasing, the need for novel therapies is rising. Sodium glucose co-transporter-2 (SGLT2) inhibitors were originally developed to treat hyperglycemia in patients with type 2 diabetes mellitus. Clinical trials with the SGLT2 inhibitor empagliflozin revealed a marked attenuation of the slope of kidney function decline, also in patients with non-diabetic CKD. The exact mechanism of this kidney sparing effect still remains to be clarified. Interestingly, cells of renin lineage (CoRL), residing in the juxtaglomerular apparatus to regulate blood pressure and fluid balance, have been demonstrated to harbor a stem cell like potential. CoRL have the ability to replenish glomerular cell number by dedifferentiating, migrating and subsequently replacing various glomerular cell types in different kidney injury mouse models. Considering that empagliflozin treatment affects renin plasma levels and electrolyte balance in patients, we hypothesized that empagliflozin could have an effect on CoRL-induced glomerular regeneration. METHOD: Experiments were performed in a Ren1cre; tdTomato lineage-trace mouse strain that expresses a tomato fluorescent label in all cells derived from renin lineage. Two kidney injury mouse models were applied; bilateral ischemia reperfusion injury (bIRI) and 5/6 nephrectomy (5/6NTx). Empagliflozin (10 mg/kg) was administered daily via oral gavage for 14 days. Subsequently, mice were sacrificed and kidneys were harvested for histological analysis. RESULTS: In both the bIRI and 5/6NTx model, empagliflozin intake led to an increase (>2-fold) of CoRL found in the intraglomerular regions compared with vehicle control littermates. These CoRL seemed to selectively differentiate towards different glomerular cell types per model: bIRI combined with empagliflozin administration resulted in an increase of claudin- (10-fold) and integrin-α8- (1.5-fold) tomato double positive cells, suggesting favored differentiation from CoRL to respectively a parietal epithelial or mesangial cell type. In contrast, in the empagliflozin treated 5/6NTx model, an increase (1.5-fold) in tomato-podocyn double positive cells was observed, implying more restocking of glomerular podocytes by CoRL in this model. CONCLUSION: SGLT2 inhibition by empagliflozin treatment leads to increased CoRL-mediated intrinsic regeneration potential and provides the kidney with different replenished cell types in different kidney disease models. Our findings demonstrate a novel mechanism via which SGLT2 inhibition might protect against kidney injury.